A study of CaH2 effectiveness as oxidation prevention in solid state sintering of single phase NiTi alloy - Mohd Zaki, Hafizah Hanim; Abdullah, Jamaluddin (Medwell Journals, 2015)
This research aims to study the conditions that may produce single phase NiTi for desirable shape memory effect under solid state by suppressing the oxide levels using CaH2 as in-situ reducing agent. A systematic comparative investigation was made on phase formation and their transformation behavior. Phase formation analysis was carried out using Scanning Electron Microscope (SEM), Energy Dispersive Spectroscope (EDS) and X-Ray Diffractometer (XRD). The transformation behaviour was studied by means of Differential Scanning Calorimetry (DSC) measurements. Thermomechanical analysis was conducted using Thermomechanical Analyzer (TMA). The study revealed that single phase NiTi was successfully formed from Ni-TiH2 specimen sintered at 930°C for 3 h under CaH2 reducing environment with good enthalpy change of ΔHA-M = 26 J g-1 and ΔHM-A = 25.5 J g-1 upon cooling and heating, respectively. However, the recovery strain reaches 0.75% at maximum 8 N applied load which is still below than the reported bulk NiTi.